Effects of Falicitation on Critical Thinking of Adult ESL Learners Engaged in Solving ILL-Structured Problems Through Asynchronous Online Forums - Mohd Bee, Aida Azlina (2011)
This quasi-experimental study examined the effects of using questions as facilitation to guide student exploration of ill-structured problems in asynchronous online forums on the critical thinking of adult ESL learners in a blended learning environment. A mixed methods approach was used to collect and analyse the data. In this pretest posttest control group format, twenty groups were randomly divided into the experimental and control groups where students worked on three different ill-structured problems consecutively. Only students in the experimental groups received facilitation as they worked through the problems. Data were collected using the Cornell Critical Thinking Test Level X (CCTT Level X) and the online forum transcripts. The statistical analysis showed that students significantly improved from the pretest to posttest after treatment (p<0.05). Data from the texts of online interaction showed that with facilitation, students were guided to identify the problem before providing solutions and to check the viability of suggested solutions before making decisions. The occurrence of critical thinking also greatly increased when students received facilitation during their discussion. The qualitative results not only substantiated the quantitative findings but also highlighted the accommodating features of asynchronous online forums that support the development of critical thinking. Both students and the facilitator had time to think and reflect on their thoughts, and the flexibility to respond at any time that was convenient for them. The asynchronous features seem favourable to adult learners. The study provides evidence that facilitating student discussion of ill-structured problems using questions promotes and develops critical thinking. It offers alternative teaching practices that make effective use of the infusion of asynchronous networks and learning instructions as educational tools in online learning environments that support constructivist principles and collaborative learning in order to develop critical thinking. Based on the findings of the study, a model was suggested using the Nine Teacher Strategies listed by Udall and Daniels for better facilitation of discussion of ill-structured problems in online learning environments.